Design and feasibility analysis of a novel auto hold system in hydrostatic transmission wheeled vehicle - Lv Chang; Jianguo Dai; Shuo Liu (Automatika, 2020)
Auto hold refers to vehicle’s function of automatic braking under shutdown condition and automatic relieving braking force when vehicle starts. This paper presents a concrete structure of the novel auto hold system of hydrostatic transmission wheeled vehicle, and deeply analyses the working mechanism and control method. To validate its feasibility, AMESim software is adopted to establish the simulation model of the auto hold system based on mathematical theories. By using the data of a certain comprehensive operation mode as input, the curve of braking force of the auto hold system is obtained through simulation. It can be known through analysis that the proposed auto hold system can realize rapid response and provides stable braking force under different road conditions. Finally, the feasibility of the proposed auto hold system is validated by comparing the simulation data with actual braking force required and the electronic vehicle parking technology. It turns out that the auto hold system can meet the requirements of all road conditions. Besides, it also can provide a fault tolerance range for real vehicle experiments, and it will not cause adverse impacts due to excessive parking brake force.